2018
DOI: 10.1504/ijstm.2018.094438
|View full text |Cite
|
Sign up to set email alerts
|

Monetary integration in the ASEAN Economic Community challenge: the role of the exchange rate on inflation in Indonesia

Abstract: The implementation of the ASEAN Economic Community (AEC) in 2015 required some form of monetary integration, such as exchange rate management. This paper investigates the role of the exchange rate on the inflation rate in Indonesia. Using the monthly data series from 1970 to 2015, we find that the nominal exchange rate affects the inflation rate at a low transmission speed rate. However, the exchange rate volatility and depreciation threshold may accelerate the speed of the exchange rate's transmission to infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
1
0
1
Order By: Relevance
“…Penelitian yang dilakukan Rahadyan & Lubis (2018), Ningsih & Kristiyanti (2018, serta Larasati & Amri (2017), memperoleh hasil bahwa kurs mempunyai pengaruh signifikan terhadap inflasi. Berdasarkan teori serta hasil-hasil penelitian terdahulu, maka dimunculkan hipotesis yang kedua: H2: Kurs berpengaruh signifikan terhadap inflasi di Indonesia periode 2015-2019.…”
Section: Kurs Dan Inflasiunclassified
“…Penelitian yang dilakukan Rahadyan & Lubis (2018), Ningsih & Kristiyanti (2018, serta Larasati & Amri (2017), memperoleh hasil bahwa kurs mempunyai pengaruh signifikan terhadap inflasi. Berdasarkan teori serta hasil-hasil penelitian terdahulu, maka dimunculkan hipotesis yang kedua: H2: Kurs berpengaruh signifikan terhadap inflasi di Indonesia periode 2015-2019.…”
Section: Kurs Dan Inflasiunclassified
“…In the future, Indonesia and Malaysia must be ready to face the Asian Economic Community (AEC). However, Indonesia is considered to be incapable and has failed to face the AEC (Permatasari, 2020;Rahadyan & Lubis, 2018) . In addition, Yaakub et al, (2020) revealed that online entrepreneurship is still in scarcity, while Lin et al, (2018), and Maliki et al, (2020) reveal weaknesses in traditional businesses.…”
Section: Introductionmentioning
confidence: 99%